Relation between participation in sport activities and drug-taking among 14 year-old primary school pupils in Slovenia - Maja Meško; Jože Štihec; Polona Kršmanc Šiško; Damir Karpljuk; Mateja Videmšek (Zdravniški Vestnik, 2010)
Purpose/Objective: The aim of this research was to establish whether there is a correlation between sport activity and drug-taking among 680 14-year-old pupils, and to establish whether the drug-sports link depends on the type of sports. Methods: We used a questionnaire with 38 variables on sports activities and drugs. The probability relations among the variables were tested by chi-square. Results: The analysis has shown that 74.6 % male and 79.3 % female pupils practise sports in their leisure time. On average, they practise sports 2 to 3 times a week. The majority of male pupils practise sports competitively, while female pupils primarily practise unorganized recreational sports. 7.3 % male and 16.6 % female pupils smoke; the majority of male pupils had the first cigarette at the age of 13, female pupils at the age of 12. 87–4 % male and 85.5 % female pupils had tried an alcohol beverage. 21.6 % male and 29.3 % female pupils had tried drugs. We have ascertained that there is some statistically significant correlation between sports activities and taking licit and illicit drugs. A statistically characteristic correlation has been established for alcohol drinking with male pupils and for smoking with female pupils. We also observed a significant correlation between organized sports as the type of sports and drug use. Conclusion: We can conclude that persistent sports inactivity in adolescence may increase the risk of alcohol use among male, and smoking among female pupils. Participation in organized sports, as opposed to unorganized and competitive sports, may reduce illicit drug use.